Ta’dīb and its implementation in children’s education, an analytical study from the prophetic hadīth - Amina Khatun,; Raudlotul Firdaus Fatah Yasin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The study aims to explore the concept of the ta’dīb (discipline) of children and the way parents and teachers discipline children from the perspective of Sunnah. It attempts to examine the social structure of muslim families, which instils in children some Islamic values and traditional standards. It is agreed that this violent approach does not align with Prophet Muhammad’s approach to disciplining children. It employs inductive and analytical methodologies in which relevant data is collected from Sunnah books (Kutub Sittah) to guide the ta’dīb concept and its application in child education. However, its use in the Sunnah stands unequivocally for discipline. Secondly, corporal punishment has hardly any relevance to the concept of ta’dīb except in exceptional cases. Third, prophetic principles of raising children according to ta’dīb include behavioural modification; developing self-esteem; motivation for seeking knowledge; the impact of naming children; learning through play; self-evaluation; and education through emotional intelligence and compassion. These multiple outcomes are expected to be beneficial in dealing with children’s welfare. Hence, the concept of ta’dīb, if defined and practised properly, can be applied to disciplining children as an Islamic methodology of children’s education, positively and politely.